FAST technique: fast atrial sheath traction technique for device closure of atrial septal defects - Haddad, Raymond N.; Kaddoura, Rachid; Kasem, Mohamed; Alsoufi, Mahmoud (Frontiers in Cardiovascular Medicine, 2023)
Background Transcatheter closure of atrial septal defects (ASDs) is well-established. However, this procedure can be challenging, requiring multiple attempts and advanced implantation maneuvers. Materials and methods From July 2019 to July 2022, patients to whom the fast atrial sheath traction (FAST) technique was applied for ASD device closure were prospectively followed up. The device was rapidly unsheathed in the middle of the left atrium (LA) to let it clamp the ASD from both sides simultaneously. This novel technique was directly applied in patients with absent aortic rims and/or ASD size-to-body weight ratio higher than 0.9 or after failed attempts of standard implantation. Results Seventeen patients (64.7% males) were involved with a median age of 9.8 years [interquartile range (IQR), 7.6–15.1] and a median weight of 34 kg (IQR, 22–44). The median ASD size on ultrasound was 19 mm (IQR, 16–22). Five (29.4%) patients had absent aortic rims, and three (17.6%) patients had an ASD size-to-body weight ratio higher than 0.9. The median device size was 22 mm (IQR, 17–24). The median difference between device size and ASD two-dimensional static diameter was 3 mm (IQR, 1–3). All interventions were straightforward without any complications using three different occluder devices. One device was removed before release and upsized to the next size. The median fluoroscopy time was 4.1 min (IQR, 3.6–4.6). All patients were discharged the next postoperative day. On a median follow-up of 13 months (IQR, 8–13), no complications were detected. All patients achieved full clinical recovery with complete shunt closure. Conclusion We present a new implantation technique to efficiently close simple and complex ASDs. The FAST technique can be of benefit in overcoming left disc malalignment to the septum in defects with absent aortic rims and in avoiding complex implantation maneuvers and the risks of injuring the pulmonary veins.